Influence of sociodemographic clinical characteristics on quality of life and distress of cancer patients - Costa, Gema; Ballester, Rafael (Psicooncología, 2010)
Several studies have examined a range of clinical and socio-demographics factors as predictors or correlates of adjustment to cancer treatment. Findings varied across different studies by which characteristics were chosen to be examined. In spite of these issues, some factors emerged like modulators to the adjustment to cancer; age, gender, educational level, marital status, length of time since diagnosis, localized of tumor, late effects of cancer and/or its treatment, type of oncology treatment. Two measures are used, quality of life and distress, to assess the different sample characteristics related to cancer treatment. Other variables, coping styles and social support, have to be considered such as mediating factors which may exacerbate or ameliorate the patient’s well-being. Particular areas have been highlighted in this literature review, initial theory research identified characteristics associated with adjustment to cancer.
Keywords: Socio-demographic characteristics; Cancer treatment; Quality of life; Distress